Reforming Juvenile Justice - Junger-Tas, Josine.; D<U+00fc>nkel, Frieder. (Springer US, 2009)
Reforming Juvenile Justice deals with fundamental, and at times, controversial issues in juvenile justice that are universal and go beyond the individual juvenile justice systems of various countries. For example: What age groups can be transfered to the adult criminal justice system and for what crimes? What can be said about the mental and moral development of juveniles in that age group? Do we know anything about the effects in terms of recidivism and reconviction by juveniles who have been penalized in the adult system? These are the kind of questions that this book, written by a group of experts on specific sub-topics in juvenile justice, tries to answer. The book concludes with a number of recommendations for improvements in juvenile justice.